Odpowiedzi

Najlepsza Odpowiedź!
2010-03-02T18:27:16+01:00
A) 2u - 10 + 15 = 3u - 12 + 10
2u - 3u = -12 + 10 + 10 - 15
-u= - 7 / :(-1)
u = 7
B) 6a - 4 - 6 = 9a - 4,5 + 0,5
6a - 9a = -4,5 + 0,5 + 4 + 6
- 3a = 6 /: (-3)
a = -2
C) -3y/3 - 3 - 2 = 4 - 4y
-3y/3 + 4y = 4 + 3 + 2
-3y/3 + 4y = 9 / *3
3(-3y/3 + 4y) = 9*3
-3y + 12 y = 27
9y = 27 / : 9
y = 3
  • Użytkownik Zadane
2010-03-02T18:27:30+01:00
2(u-5) + 15 =3(u - 4) + 10
2u-10+15=3u-12+10
2u+5=3u-2
-u=3
u=-3

2 (3a - 2) - 6 = 4,5 (2a - 1 ) + 0,5
6a-4-6=9a-4,5+0,5
6a-10=9a-4
-3a=6
a=-2

-3 (y/3 + 1) - 2= 4 (1 - y)
-y-3-2=4-4y
-y-5=4-4y
-5y=9
y=-9/5
y=-1⅘